The impact of the Internet on reference services in higher education libraries in South Africa - Darries, Fatima (Library and Information Studies Centre (LISC), 2014)
Internet access has become an indicator of a country's socio-economic status in the Information society. Libraries of higher education institutions support the parent institutions' objective to produce graduates able to function in this society. Consequently, the Web, the most popular part of the Internet, has become ubiquitous in reference services. This study investigates the impact of the Internet on reference services by exploring the following areas: user Internet access and training in the library, use and integration of the Internet as an information tool in reference services and the Internet training and knowledge of reference librarians.